Pride and shame in child and family social work : emotions and the search for humane practice - Gibson, Matthew (Policy Press, 2019)
What role does emotion play in child and family social work practice? In this text, researcher Matthew Gibson reviews the role of shame and pride in social work, providing invaluable new insights into the role of these emotions within professional practice. The author shows how these emotions, which are embedded within the very structures of society but experienced as individual phenomena, are used as mechanism of control in relation to both professionals themselves and service users. Examining the implications of these emotional experiences in the context of professional practice and the relationship between the individual, the family and the state, the work calls for a more humane form of practice, rooted in more informed policies that take in to consideration the realities and frailties of the human experience.